Integration of physics based weight models into rotorcraft design sizing - Govindarajan, B.; Sridharan, A.; Avera, M. (My University, 2017)
The availability of an accurate empty weight model for each rotorcraft component is critical for synthesizing efficient vehicles, because over-designing one component in a flying platform results in a higher take-off weights, more installed power and smaller reduced useful load fraction. Traditionally, these models are synthesized using statistical data, which are unavailable for unconventional, medium-scale and next-generation VTOL configurations. This paper presents a methodology for design sizing of unconventional rotorcraft using physics-based weight models for the primary load-carrying members. This methodology is demonstrated for a quad-rotor bi-plane tailsitter hybrid configuration, which can operate in both fixed-wing and airplane mode. A beam lattice framework for the airframe structure, and the spar geometry in the rotor blade are iteratively adjusted during design sizing to accommodate the expected wing loads and rotor blade loads. Using this analysis, a consistent combination of vehicle macro-dimensions (rotor radius, tip speed, wing span) as well as detailed design parameters (spar height, skin thickness and cross-section weight) are obtained simultaneously.